2019
DOI: 10.32504/hspj.v3i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Fungsi pengarahan kepala ruang dalam pelaksanaan discharge plannning perawat di RS PKU Muhammadiyah Yogyakarta

Abstract: Discharge planning is one indicator of ongoing nursing services that if performed well by the nurses will be able to improve the quality of nursing services and patient satisfaction. One influential factor is the leadership of the head nurse, especially in the function of directing to nurses when carrying out discharge planning. The directional function carried out by the head nurse is in the form of giving motivation, supervision and conflict management. The purpose of this study was to determine the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The directive function carried out by the head of the room is in the form of providing motivation, supervision, and conflict management. 11 Other research shows that more than half (53.3%) of the head of the room carried out the supervision and documentation which was done completely and incompletely, the same amount (50%) was carried out by the executive nurse. The results of bivariate analysis with chi-square were obtained (p = 0.021), it can be concluded that there is a relationship between the supervision of the head of the room and the documentation of nursing care in the inpatient room of RSI Ibnu Sina Bukittinggi.…”
Section: Discussionmentioning
confidence: 99%
“…The directive function carried out by the head of the room is in the form of providing motivation, supervision, and conflict management. 11 Other research shows that more than half (53.3%) of the head of the room carried out the supervision and documentation which was done completely and incompletely, the same amount (50%) was carried out by the executive nurse. The results of bivariate analysis with chi-square were obtained (p = 0.021), it can be concluded that there is a relationship between the supervision of the head of the room and the documentation of nursing care in the inpatient room of RSI Ibnu Sina Bukittinggi.…”
Section: Discussionmentioning
confidence: 99%
“…Kepala ruangan melakukan motivasi melalui pendampingan dalam proses serah terima serta melakukan komunikasi dua arah yaitu memberikan masukan-masukan untuk peningkatan pelaksanaan serah terima yang lebih baik. Suasana yang memotivasi dapat diciptakan dari fungsi pengarahan kepala ruangan (Imallah & Khusnia, 2019). Motivasi penting terutama bagi perawat dalam mencapai serta meningkatkan kualitas layanan keperawatan.…”
Section: Pembahasanunclassified